The Association of Serum AIM2 Level with the Prediction and Short-Term Prognosis of Coronary Artery Disease - Zhang, Wenkang; Yan, Gaoliang; Xu, Chunyang; Tang, Chengchun (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Objective. Coronary artery disease (CAD), one of the commonest cardiovascular diseases, has high morbidity and mortality. Absent in melanoma 2 (AIM2) is involved in atherosclerosis, and no clinical trials have explored the association between AIM2 and CAD. Therefore, this study was aimed at evaluating the predictive and short-term prognostic value of AIM2 for CAD. Methods. 279 patients who underwent coronary angiography were enrolled in this study. The AIM2 level was detected from the serum of collected artery blood samples. The association of serum AIM2 level with the prediction and short-term prognosis of CAD was further assessed. Results. The serum AIM2 level of the CAD group was significantly higher than the control group (5.5±2.1 vs. 3.7±1.7; p<0.001). AIM2 was demonstrated to be the risk factor of CAD [odds ratio, 1.589; 95% confidence interval (CI), 1.346-1.876; p<0.001]. The area under the receiver operating characteristic (ROC) curve of 0.738 showed the diagnostic value of AIM2 in CAD. Additionally, AIM2 was an independent predictor of major adverse cardiovascular events (hazard ratio, 1.453; 95% CI, 1.086-1.945; p=0.012), and CAD patients with high AIM2 levels (>4.9 ng/mL) had a markedly lower survival rate (log-rank p=0.040). Conclusions. The serum AIM2 level>4.9 ng/mL can predict CAD to a certain extent. AIM2 might be an independent predictor of its short-term poor prognosis.